Population dynamics of the glacial relict amphipod Monoporeia affinis in a subarctic lake ... - Maximov, Alexey (Dryad, 2021)
Seasonal and interannual (2002–2019) variations in the abundance (ind. m-2) and population structure of the glacial relict amphipod Monoporeia affinis in a small subarctic Lake Krivoe (North-West of the Russian Federation) are presented. The study site (66⁰ 20.774′ N and 33⁰ 37.77′ E) was situated in the sublittoral zone at the depth of 8.5 m. Materials were collected from June 2002 to December 2019 mainly during the ice-free period (late May – October) as a rule, 4–5 times a season. In addition, the next data sets used in interpretation of population dynamics are presented: (1) Changes in mean near- bottom (7–8 m) temperature (± range) and mean chlorophyll a (0–7 m) concentration (µg l-1) gat study site during open-water period (May – October) in 2002–2019. (2) Changes in mean annual abundance (ind. m-2) of main macrobenthic taxa at study site in 2002–2019. ... : Materials were collected at one site (depth 8.5 m) from 2002 to 2019 mainly during the ice-free period (late May – October) as a rule, 4–5 times a season. Benthic samples were taken by standard Van-Veen grab (area 0.025 m2) in five replicates and were sieved through a screen with mesh sizes of 0.25 mm. In the laboratory, all macroinvertebrates were sorted and preserved in 70% ethanol. To estimate the age structure of Monoporeia affinis population, the body length (distance between rostrum and telson base) of preserved amphipods was later measured to the nearest 0.1 mm. Altogether about 4 000 (that is 50 individuals per sampling occasion) amphipods were measured. The age groups were separated subjectively based on histograms of length-frequency distribution. Near-bottom (7–8 m) temperature during the ice-free period was measured on a biweekly or monthly basis. The mean temperature was calculated by integrating these data. The concentration of chlorophyll from 2010 was obtained from monthly integral water ...